Neuroanatomical Assessment of the Integrin β3 Mouse Model Related to Autism and the Serotonin System Using High Resolution MRI - Ellegood, Jacob; Henkelman, R. M.; Lerch, Jason P. (Frontiers in Psychiatry, 2012)
The integrin β3 (ITGβ3) gene has been associated with both autism and the serotonin system. The purpose of this study was to examine the volumetric differences in the brain of an ITGβ3 homozygous knockout mouse model compared with a corresponding wild-type mouse using high resolution magnetic resonance imaging and detailed statistical analyses. The most striking difference found was an 11% reduction in total brain volume. Moreover, 32 different regions were found to have significantly different relative volumes (% total brain volume) in the ITGβ3 mouse. A number of interesting differences relevant to autism were discovered including a smaller corpus callosum volume and bilateral decreases in the hippocampus, striatum, and cerebellum. Relative volume increases were also found in the frontal and parieto-temporal lobes as well as in the amygdala. Particularly intriguing were the changes in the lateral wings of the dorsal raphe nuclei since that nucleus is so integral to the development of many different brain regions and the serotonin system in general.